2018
DOI: 10.1111/jnc.14329
|View full text |Cite
|
Sign up to set email alerts
|

Role of G protein‐coupled receptor kinase 2 in oxidative and nitrosative stress‐related neurohistopathological changes in a mouse model of sepsis‐associated encephalopathy

Abstract: Sepsis-associated encephalopathy (SAE), characterized as diffuse brain dysfunction and neurological manifestations secondary to sepsis, is a common complication in critically ill patients and can give rise to poor outcome, but understanding the molecular basis of this disorder remains a major challenge. Given the emerging role of G protein-coupled receptor 2 (GRK2), first identified as a G protein-coupled receptor (GPCR) regulator, in the regulation of non-G protein-coupled receptor-related molecules contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 51 publications
3
21
0
Order By: Relevance
“…They revealed that GRK2 strongly regulated the expression/activation of IRF1as well as the activation of the STAT pathway, leading to increased transcription of iNOS, when TLR-3, TLR-4, or TLR-9 was stimulated in microglial cells. This extends their previous report showing that GRK2 plays a critical role in iNOS gene t r a n s c r ip t i o n i n m i c r o g l i a l c e l l s s t im u l a t e d wi t h lipopolysaccharide (Kawakami et al, 2018). Their findings highlight a novel pathological role of GRK2 in regulating inflammatory signaling in microglia with a potential therapeutic window for some neuroinflammatory disorders.…”
supporting
confidence: 86%
“…They revealed that GRK2 strongly regulated the expression/activation of IRF1as well as the activation of the STAT pathway, leading to increased transcription of iNOS, when TLR-3, TLR-4, or TLR-9 was stimulated in microglial cells. This extends their previous report showing that GRK2 plays a critical role in iNOS gene t r a n s c r ip t i o n i n m i c r o g l i a l c e l l s s t im u l a t e d wi t h lipopolysaccharide (Kawakami et al, 2018). Their findings highlight a novel pathological role of GRK2 in regulating inflammatory signaling in microglia with a potential therapeutic window for some neuroinflammatory disorders.…”
supporting
confidence: 86%
“…CLP-induced sepsis is regarded as a highly clinically relevant model of polymicrobial sepsis, because it reproduces many hallmarks of sepsis occurring in human patients (Hubbard et al 2005 ). The surgical procedure to generate CLP-induced sepsis was conducted according to our previous reports (Tomita et al 2015 ; Kawakami et al 2018 ; Yamashita et al 2018 ). In brief, male BALB/c mice (Sankyo Lab Service, Tokyo Japan), 8–12 weeks old, were anesthetized with 3–4% sevoflurane by inhalation, and a middle abdominal incision was made.…”
Section: Methodsmentioning
confidence: 99%
“…Values were normalized to the housekeeping gene GAPDH according to the manufacturer’s protocol (MX3000P real-time PCR system; Agilent Technologies Inc., Santa Clara, CA, USA). Additional details are described by our laboratory (Kawakami et al 2018 ; Yamashita et al 2018 ; Suzuki et al 2018 ). The PCR primers were designed as follows: forward 5’-TGCAGATTATGCGGATCAAACC-3′ and reverse 5′-TGCATTCACATTTGTTGTGCTGTAG-3′ for VEGF, forward 5′-CAGGCCCAGTTTCTGCCATT-3′ and reverse 5′-TTCCAGCTCAGCGTGGTCGTA-3′ for VEGFR1, forward 5′-CCAGCAAAAGCAGGGAGTCTGT-3′ and reverse 5′-TGTCTGTGTCATCGGAGTGATATCC-3′ for VEGFR2, and forward 5′-TGTGTCCGTCGTGGATCTGA-3′ and reverse 5′-TTGCTGTTGAAGTCGCAGGAG-3′ for glyceraldehyde-3-phosphate dehydrogenase (GAPDH).…”
Section: Methodsmentioning
confidence: 99%
“…TNF-α and IL-6 are early indicators of sepsis (Kruttgen and Rose-John, 2012), and their concentrations are associated with outcomes in patients with sepsis. NO, and ROS play key roles in the pathogenesis of sepsis and also indicate oxidative stress and nitric stress in SAE, respectively (Kawakami et al, 2018;Neri et al, 2016). The results of this study showed that the concentrations of these indicators increased in the test groups compared with the control group.…”
Section: Discussionmentioning
confidence: 52%